Giant cementoblastoma involving multiple teeth: A rare case report and review of differential diagnoses - Dwi Noviyanti, MD; Atta Kuntara, MD; Eka Marwansyah Oli'i, MD; Hasrayati Agustina, MD (Radiology Case Reports, 2024)
Cementoblastoma, a rare odontogenic benign tumor characterized by calcified cementum-like deposits produced by cementoblasts fused with the tooth root, represents a minute proportion of all odontogenic tumors, with a prevalence ranging from less than 1% to 6.2%. We present a case of a 19-year-old female experiencing pain, progressive swelling, and facial asymmetry in the left lower region over the 1 year ago. Physical examination revealed diffuse swelling in the left mandibular area, demonstrating tenderness and bony hardness on palpation. Radiographic findings displayed a giant, well-defined, relatively round, radiopaque mass, partially delineated by a thin radiolucent halo, and adhered to the roots of the teeth. Computed Tomography imaging revealed an osteoblastic hyperdense mass with extensive buccal and lingual extension. Sagittal images illustrated the mass's continuity with the root apex of the first molar, accompanied by a well-defined hypodense border. A biopsy confirmed the diagnosis of cementoblastoma, leading to the patient undergoing a left hemimandibulectomy. Given the various periapical radiopaque lesions that serve as potential differential diagnoses for cementoblastoma, the ability of the radiologist to distinguish their imaging characteristics plays a crucial role in determining an accurate diagnosis.